2022
DOI: 10.3389/fncel.2022.867267
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome and Gut Endocannabinoid System in the Regulation of Stress Responses and Metabolism

Abstract: The endocannabinoid system, with its receptors and ligands, is present in the gut epithelium and enteroendocrine cells, and is able to modulate brain functions, both indirectly through circulating gut-derived factors and directly through the vagus nerve, finally acting on the brain’s mechanisms regarding metabolism and behavior. The gut endocannabinoid system also regulates gut motility, permeability, and inflammatory responses. Furthermore, microbiota composition has been shown to influence the activity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 301 publications
(435 reference statements)
0
25
0
Order By: Relevance
“…There is no doubt that the microbiota affects gut physiology and its role in the gut brain-axis has been convincingly established ( 75 ). Many physiological roles of intestinal microorganisms are associated to the regulation of the intestinal endocannabinoid tone [the so called endocannabinoidome ( 49 ) as extensively described in recent exhaustive reviews ( 76 78 ). There is increasing evidence that both selected intestinal microorganisms and bioactive lipids covary in pathological conditions such as obesity, type 2 diabetes and inflammation ( 76 ).…”
Section: Intestinal Microbiota Interactions With the Endoca...mentioning
confidence: 99%
See 2 more Smart Citations
“…There is no doubt that the microbiota affects gut physiology and its role in the gut brain-axis has been convincingly established ( 75 ). Many physiological roles of intestinal microorganisms are associated to the regulation of the intestinal endocannabinoid tone [the so called endocannabinoidome ( 49 ) as extensively described in recent exhaustive reviews ( 76 78 ). There is increasing evidence that both selected intestinal microorganisms and bioactive lipids covary in pathological conditions such as obesity, type 2 diabetes and inflammation ( 76 ).…”
Section: Intestinal Microbiota Interactions With the Endoca...mentioning
confidence: 99%
“…The microbiota also modulates intestinal eCB tone; as an example, Rousseaux et al ( 85 ) showed that the expression of intestinal epithelial CB 2 receptor increases when mice or rats are orally administered the bacterium Lactobacillus acidophilus . More recently it was found that the bacterium Akkermansia muciniphila is a prominent regulator of the gut eCB tone, gut permeability, and secretion of gut peptides ( 86 ); see also ( 78 ) for a comprehensive review. The role of A. muciniphila in pathological conditions has also been investigated.…”
Section: Intestinal Microbiota Interactions With the Endoca...mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have described the use of prebiotics, probiotics, or both in treating anxiety and depression both in animal and human studies [47,[65][66][67][68][69][70]. Notably, in vagotomized mice, probiotic-related effects on neurochemical changes as well as on behavior were abolished, again suggesting a role of the vagus nerve in these beneficial reactions [65].…”
Section: Potential Interventions Targeting the Ecs In Gi And Mood-rel...mentioning
confidence: 99%
“…103 Probiotic treatment increased AEA in the jejunum, whereas antibiotics reduced its levels in the duodenum. 99 Dysbiotic mice showed increased expression of CB2R and reduced CB1R expression in the colon. 104 Mutations in the Myd88 gene disrupted toll-like receptor-mediated bacterial-host interactions, resulting in changes in CB1R messenger RNA levels in the colon.…”
Section: Colonmentioning
confidence: 99%